2018
DOI: 10.1002/slct.201800918
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Conformation of Entrapped Protein inside the Reverse Micellar Confinement Based on the Amino Acid Derived Ionic Liquid

Abstract: Owing to superior surface‐activity and versatility in functionalization compared to conventional surfactants, surface‐active ionic liquids (SAILs) gained immense interest in recent years. Toxicity and biodegradation remain central issues while dealing with the SAILs and thus, the quest for synthesis of greener SAILs is increasing day by day. Keeping in view of the importance of SAIL's performance, we undertook the present study for the formulation of reverse micelles (RMs) using biodegradable L‐proline propyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…LYZ is found to retain its enzyme activity with partial change in the 2°structure when extracted into the buffer after heat treatment. The results obtained here, along with previous reports on reverse micelles, 55,56 bilayer structures, 34 and microemulsions 35 and aqueous ILs 57,58 showing enzyme and protein stability, respectively, at room temperature, provide a new platform to design and construct novel thermally stable MEs comprising biobased ILs as polar, nonpolar, and SAIL for diverse biomedical applications.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…LYZ is found to retain its enzyme activity with partial change in the 2°structure when extracted into the buffer after heat treatment. The results obtained here, along with previous reports on reverse micelles, 55,56 bilayer structures, 34 and microemulsions 35 and aqueous ILs 57,58 showing enzyme and protein stability, respectively, at room temperature, provide a new platform to design and construct novel thermally stable MEs comprising biobased ILs as polar, nonpolar, and SAIL for diverse biomedical applications.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
“…33,34 Following that, the studies on stabilization of bovine serum albumin in aqueous pool of MEs comprising biobased SAIL and cyclohexane have been derived. 35 Nevertheless, the use of cyclohexane renders the MEs toxic and thermally unstable. Therefore, the nanointerfaces of relatively less toxic and thermally stable MEs comprising ILs (nonpolar) or SAILs (surfactant) in conjunction with organic solvents with very low vapor pressure and cytotoxicity, 36−39 for example, ethylene glycol (EG) (polar phase), are expected to offer a new platform for high-temperature enzyme stabilization.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic liquids (ILs) have numerous potential applications in biochemistry and biomedical technology. ILs have been used as biomaterials, for antibiotics enhancement, , for enzyme modulation for pharmaceutical and industrial applications, and in drug delivery. , IL molecular ions in aqueous solution can exhibit subtle and sensitive interactions with biological or biologically active molecules that can in principle be tuned in an IL cation/anion mix-and-match strategy. Such a strategy could be utilized to develop selective protein stabilization or destabilization materials for protein engineering applications. ILs as solution additives could stabilize desired proteins and destabilize unwanted proteins or destabilize proteins to promote unfolding and materials self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have reported IL-induced structural and stability changes of α-helical proteins such as myoglobin, lysozyme, chymotrypsin, and bovine serum albumin. ,, ILs in aqueous solution at less than ∼1 M (about 20% by volume) often do not denature these proteins but destabilize them as reflected in unfolding free energies (Δ G unfolding ) and thermal melting temperatures. ,, Protein stabilization and/or destabilization by ILs in aqueous solution is often explained with the Hofmeister anion series, , but even small proteins (most notably myoglobin) may not exactly follow this series. , Furthermore, hydrophobic ILs can aggregate like surfactants, and proteins may partition between hydrophobic and aqueous phases. ,,,,, Studies on β-sheet proteins have also yielded interesting fundamental results. ILs alter β-sheet aggregation in β-amyloid and silk proteins, which provides interesting applications for inhibiting amyloid formation. The β-barrel green fluorescent protein has been utilized in ILs for reporting biomass solubilization, which suggests that the β-barrel structure is stable in the presence of ILs .…”
Section: Introductionmentioning
confidence: 99%